2004
DOI: 10.1124/jpet.104.073767
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of M2Muscarinic Acetylcholine Receptor Expression and Signaling by Prolonged Exposure to Allosteric Modulators

Abstract: The effects of prolonged exposure of M 2 muscarinic acetylcholine receptors (mAChRs), stably expressed in Chinese hamster ovary cells, to the allosteric modulators gallamine, alcuronium, and heptane-1,7-bis (dimethyl-3Ј-phthalimidopropyl)-ammonium bromide (C 7 /3Ј-phth) were compared with the effects of the agonist carbachol (CCh) and antagonists atropine and Nmethylscopolamine (NMS). Intact cell saturation binding assays using [3 H]NMS found that pretreatment of the cells for 24 h with CCh caused a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
30
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 32 publications
2
30
0
Order By: Relevance
“…In addition to BQCA, modulation of mAChR internalization has been demonstrated previously by the mAChR negative allosteric ligand gallamine at the M 2 mAChR and by LY2033298 at the M 4 mAChR. Gallamine decreases CCh-induced M 2 mAChR internalization and upregulates cell surface receptor levels (41). In contrast, LY2033298 potentiates ACh-induced M 4 mAChR internalization to a greater extent than would be predicted from acute signaling assays, effectively demonstrating a biased action toward regulatory pathways (10).…”
Section: Discussionmentioning
confidence: 74%
“…In addition to BQCA, modulation of mAChR internalization has been demonstrated previously by the mAChR negative allosteric ligand gallamine at the M 2 mAChR and by LY2033298 at the M 4 mAChR. Gallamine decreases CCh-induced M 2 mAChR internalization and upregulates cell surface receptor levels (41). In contrast, LY2033298 potentiates ACh-induced M 4 mAChR internalization to a greater extent than would be predicted from acute signaling assays, effectively demonstrating a biased action toward regulatory pathways (10).…”
Section: Discussionmentioning
confidence: 74%
“…Likewise, the peptide ASLW has been shown to activate the chemokine CXCR4 receptor in a manner that is likely to be allosteric (Sachpatzidis et al, 2003). For the mAChRs, Jakubik et al (1996) demonstrated that gallamine and alcuronium could promote receptor activation, but these results are not consistently reproduced May et al, 2005) and may reflect the requirement of particular stoichiometries of receptor to G protein (Jakubik et al, 1998). Earlier radioligand binding studies suggested that the partial agonist McN-A-343 was also an allosteric modulator of M 2 mAChRs , although a subsequent functional study was unable to conclude whether this compound interacted allosterically with very high negative cooperativity or via simple orthosteric competition when tested against carbachol (Christopoulos and Mitchelson, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of allosteric ligands on GPCR regulation are poorly defined at present and appear to be receptor subtype-specific. Thus, previous work exploring long-term exposure to allosteric modulators of the M 2 mACh receptor revealed an up-regulation of receptor numbers (May et al, 2005), whereas chronic exposure to AC260584, an allosteric agonist structurally related to AC-42 (Spalding et al, 2002), resulted in no significant changes in M 1 mACh receptor expression (Davis et al, 2005). In contrast, and looking beyond the mACh receptor subfamily, activation of the type 7 metabotropic glutamate receptor by the allosteric agonist AMN082 caused receptor internalization in a manner similar to that elicited by the orthosteric ligand, L-AP4 (Pelkey et al, 2007).…”
mentioning
confidence: 91%
“…It is possible for this AC-42/atropine effect to be explained by a complex allosteric interaction, where AC-42 has positive cooperativity with respect to atropine in terms of efficacy, with the functional output in this case being a decrease in receptor internalization/degradation. Both AC-42 and atropine have been independently shown to increase cell-surface mACh receptor expression (May et al, 2005), indicating that both are "agonists" with respect to this endpoint. Even if AC-42 and atropine are highly negatively cooperative with respect to binding (although this has not been directly measured here), if they exhibit a sufficiently positive efficacy cooperativity, then the decrease in constitutive receptor recycling mediated by atropine may be facilitated in the presence of AC-42.…”
mentioning
confidence: 99%
See 1 more Smart Citation